Additive manufacturing of aerospace composite structures : fabrication and reliability - Elhjjar, Rani (SAE International, 2017)
Additive manufacturing of aerospace composite structures: fabrication and reliability introduces the reader to the current state of technologies involved in processing and design of polymer-reinforced fiber composites using additive manufacturing's automated fiber placement methods, through ten seminal SAE International papers.
"Aerospace"--Cover
Keywords: Additive manufacturing.; Aerospace industries.; Composite materials.; elektronické knihy; electronic books